Inadequate diet mixing time reduces nursery pig performance - Groesbeck, C.N.; Neill, C.R.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Although the importance of thoroughly mixing diets is often emphasized, little data is available to quantify the impact of inadequate mixing on pig growth performance. Therefore, a 28-d trial was conducted to evaluate the effects of mixing time on growth performance of nursery pigs. A total of 180 weanling pigs (13.9 ± 1.8 lb BW, 21± 3 d of age) were used, with 6 pigs per pen and 6 pens per treatment. Experimental treatments consisted of mixing a diet for 0, 30, 60, 120 or 330 s in a horizontal ribbon mixer. Diets were fed in two phases (d 0 to 14 and 14 to 28), with diets in both phases containing relatively large amounts of lowinclusion ingredients such as synthetic amino acids, zinc oxide, and phytase. Diets in Phase 1 also contained 3.75% fish meal and 15% dried whey. Eight samples were collected from the mixer at the completion of the mixing time for each batch of feed to determine a coefficient of variation (CV). Each bag (50.0 lb) was labeled (first to last) and sampled to determine the degree of mixing that occurred as feed was conveyed from the mixer to the bagger. Each pen of pigs was then assigned a bag of feed. Bags were distributed in the order bagged (1, 2, 3, etc.). As feed was needed, the next chronological bag of feed was then added. Mixer CV values were 178, 38, 26, 21, and 5% for Phase 1 and 172, 79, 60, 48, and 26% for Phase 2 as mixing time increased. Bag CV values were 26, 20, 16, 11, and 7% for Phase 1 and 56, 45, 40, 33, and 12% for Phase 2 as mixing time increased, indicating the degree of mixing that takes place as feed is conveyed from the mixer to the bagger. Growth performance was improved as mixing time increased (linear, P<0.01) in both phases. From d 0 to 28, increasing mix time increased (linear, P<0.01) ADG (0.73, 0.89, 0.90, 0.94, and 1.02 for 0, 30, 60, 120, and 330 s, respectively). Increasing mixing time also improved F/G (linear, P<0.01; quadratic, P<0.07; 1.55, 1.40, 1.32, 1.33, 1.30 for 0, 30, 60, 120, and 330 s, respectively). With greater use of lowinclusion ingredients such as synthetic amino acids in swine diets, these data demonstrate that inadequate mixing reduces nursery pig performance.
Swine research, 2005 is known as Swine day, 2005
Keywords: Growth; Mixer efficiency; Nursery pig; Swine